THE REAL CHALLENGES IN TEACHING ENGLISH - Dilrabo Yarmatova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Per the latest state educational standards, teachers are required to cultivate a persona primarily by instilling universal educational practices. These practices serve as a consistent foundation for the educational process. One key aspect of these practices involves empowering students to autonomously engage in exercises, establish educational objectives, seek and utilize appropriate resources, and assess both the process and outcomes of their endeavors.